2002
DOI: 10.1038/sj.bmt.1703621
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of ABO incompatibility in allogeneic hematopoietic stem cell transplantation

Abstract: Summary:Aside from causing hemolytic reactions the ABO blood group system does not have an impact on outcome after allogeneic bone marrow or peripheral blood stem cell transplantation (SCT). However, only a few studies have addressed the effect of ABO incompatibility on the incidence of GVHD, time to engraftment, relapse and survival. Therefore, we performed a retrospective twocenter analysis of 562 consecutive patients receiving allogeneic SCT, including 361 ABO-identical, 98 minor, 86 major and 17 bidirectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
106
7
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(123 citation statements)
references
References 25 publications
7
106
7
3
Order By: Relevance
“…Conflicting data still exist as to the influence of ABO mismatch on GVHD and survival. Bacigalupo et al 29 and Stussi et al 30 suggested that ABO incompatibility represents a risk factor for aGVHD after allogeneic SCT. A possible reason may be that broadly distributed ABO Ags may damage the host endothelium, potentially triggering GVHD in incompatible SCT.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting data still exist as to the influence of ABO mismatch on GVHD and survival. Bacigalupo et al 29 and Stussi et al 30 suggested that ABO incompatibility represents a risk factor for aGVHD after allogeneic SCT. A possible reason may be that broadly distributed ABO Ags may damage the host endothelium, potentially triggering GVHD in incompatible SCT.…”
Section: Discussionmentioning
confidence: 99%
“…2,8,[12][13][14] Immunological effects of ABO BD and MJ mismatch include acute haemolysis, pure red cell aplasia and delayed engraftment, leading to increased transfusion requirements. [15][16][17] In HSCT patients with ABO MN mismatch, acute or delayed haemolysis occur in up to 15-30% due to the development of passenger lymphocyte syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…21 The impact of ABO mismatch on transplant outcomes is variable, with a number of small and heterogeneous studies in the literature. 4,8,[22][23][24][25][26][27][28][29] Of the larger studies, a French registry study of 1108 RIC HSCT patients reported that MN ABO incompatibility was associated with reduced OS. 30 In the RIC subgroup of the largest registry study to date, Kimura et al 2 reported increased transplantrelated mortality (TRM) for MN, MJ and BD ABO-mismatched patients.…”
Section: Introductionmentioning
confidence: 99%
“…There is an intense debate about the impact on outcome, severity of hemolysis, association with graft-versus-host disease and survival after blood group-incompatible stem cell transplantation. [1][2][3] Since blood group antigens are inherited independently of the human leukocyte antigen (HLA) complex, 4 ABO incompatibility between donor and recipient is observed in about 30% of HSCT. 5 Red cell incompatibility is classified according to whether donor's isohemagglutinins, isoantigens or both are incompatible with those of the recipient.…”
mentioning
confidence: 99%